Pengaruh Keadilan Distribusi, Prosedural dan Interaksional terhadap Kepuasan Konsumen Mahasiswa di Surabaya - Wulani, Fenika (Fakutas Ekonomi Unika Widya Mandala Surabaya, 2007)
This study examines the effect of distribution, procedural, and Interactional justice on customer satisfaction Data were collected from 183 students on 4 universities in Surabaya. This study finds that interactional and procedural justice has effect on customer satisfaction. However, this study that distribution justice has no effect on customer satisfaction.